2019
DOI: 10.1182/blood-2019-125944
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for Double Hit Lymphoma Patients Identified Via Routine Vs Selective Testing for MYC Rearrangement

Abstract: Introduction Patients (pts) diagnosed with double hit lymphoma (DHL) are reported to experience poor survival outcomes following first-line treatment with R-CHOP, although survival may be improved with receipt of intensive front-line immunochemotherapy. These results may be altered by selection bias, as prior retrospective series of DHL pts did not report performing routine cytogenetic testing to identify those with DHL. We hypothesized that outcomes might differ for DHL pts identified after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…On the other hand, this may result in a bias with a dilution of the most aggressive cases over time. Frosh et al showed that DHL identified with a routine FISH technique resulted in longer patient survival than DHL identified by selective FISH 15 . Such generalization of FISH technique however raises the question of the management of localized cases of DHL and THL (Stage I/II Ann Arbor).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this may result in a bias with a dilution of the most aggressive cases over time. Frosh et al showed that DHL identified with a routine FISH technique resulted in longer patient survival than DHL identified by selective FISH 15 . Such generalization of FISH technique however raises the question of the management of localized cases of DHL and THL (Stage I/II Ann Arbor).…”
Section: Discussionmentioning
confidence: 99%
“…DHITsig positive patients had dismal outcomes after being treated with R-CHOP in terms of DSS (BioElectric Massage) (pos vs neg, 63% vs 90%), 5-year PFS (pos vs neg, 53% vs 79%), and OS (pos vs neg, 60% vs 83%). Several literature highlighted the importance of risk stratification depending on molecular features like GEP (gene expression profile), instead of merely genetic translocation status, to avoid missing out on a cluster of high-risk patients while exposing low-risk ones to excessive therapies [ 27 , 28 ].…”
Section: Diagnosis Prognosis and Current Treatmentmentioning
confidence: 99%
“…To avoid the late diagnosis, the study result supports the performance of the routine FISH test in all DLBCL patients, which considerably improves the outcome of DHL (ST vs RT: 2-year RFS, 38% v 70% and 2-year overall survival, 38% v 74%). At the same time, routine testing identified a cohort of low-risk DHL patients and the lack of benefit from intensive immunochemotherapy [ 28 ]. Independent research further stratifies DHL into high-risk and low-risk (DHIT + SIG) subgroups, suggesting tremendous heterogenicity lies in the DHL cohort [ 26 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Despite there being no relevant differences in measured baseline clinicopathologic features or in rates of treatment with intensive first-line immunochemotherapy, patients with DHL who were identified by ST as opposed to RT had a 2-year relapse-free survival (RFS) of 43% versus 70% and a higher risk of 2-year relapse and death, even when accounting for clinical, pathologic, and treatment factors in a multivariable model. 11 These results did not change when considering only the 80% of patients treated with intensive immunochemotherapy in each group (2-year RFS, 38% v 70% and 2-year overall survival, 38% v 74%). In addition, for patients in the RT cohort, those who received R-CHOP compared with those who received intensive first-line immunochemotherapy experienced similar 2-year RFS (80% v 70%) as well as 2year overall survival (67% v 74%), suggesting a possible lack of survival benefit from using intensive first-line immunochemotherapy in the RT cohort.…”
mentioning
confidence: 89%